THE MIMETIC AND EXPRESSIVE ACT VALUES ANALYSIS IN THE “BE” (DELUXE EDITION) ALBUM MUSIC BY BTS (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this study is to comprehend the metaphoric and expressive analysis found in BTS's album "BE" (Deluxe Edition), as well as the implications of this analysis' findings. BTS has catchy songs that are inspiring and many of their songs are particularly motivating for listeners; their lyrics specifically encourage each member to confront the current state of the pandemic. The research being used here is qualitative research using the pendekatan mimesis and ekspresif techniques. By conducting the aforementioned analysis, the audience will examine their morals and beliefs in light of the real-world images that are embedded in the song's lyrics. After doing this study, the participants selected eight songs that included mimetic analysis within a few lyric sections and two songs that included expressive analysis within a few lyric sections.